The complete mitochondrial genome of Megalurothrips usitatus (Bagnall 1913) (Thysanoptera: Thripidae) and its phylogenetic analysis. Issue 6 (3rd June 2022) - Cheng, Jiang-Hui; Li, Xiao-Wei; Chen, Li-Min; Han, Hai-Bin; Lu, Yao-Bin; Ruan, Yong-Ming
Abstract: Megalurothrips usitatus is a serious pest on Vigna unguiculata . In this study, the complete mitochondrial genome sequence of M. usitatus was characterized and its phylogenetic relationship within the Order Thysanoptera was determined. The mitochondrial genome of M. usitatus was a circular molecule of 15426 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and the control region. It showed the typical insect mitochondrial genome arrangement. The AT content of the whole genome was 77.69% and the length of the control region was 567 bp with 78.66% AT content. The Maximum likelihood (ML) phylogenetic analysis based on mitochondrial protein-coding genes of 17 insect speciesshowed that M. usitatus is closest to Frankliniella occidentalis .